Concurrent Validation and Reference Values of Gluteus Medius Clinical Test - Amanda S S Teixeira; Paula L Silva; Sabrina P Cintra; Fernanda Viegas; Luciana D Mendonça; Natália F N Bittencourt (International Journal of Sports Physical Therapy)
# Context